Dnmt1 binds and represses genomic retroelements via DNA methylation in mouse early embryos. Issue 15 (15th July 2020) - Min, Byungkuk; Park, Jung Sun; Jeong, Young Sun; Jeon, Kyuheum; Kang, Yong-Kook
Abstract: Genome-wide passive DNA demethylation in cleavage-stage mouse embryos is related to the cytoplasmic localization of the maintenance methyltransferase DNMT1. However, recent studies provided evidences of the nuclear localization of DNMT1 and its contribution to the maintenance of methylation levels of imprinted regions and other genomic loci in early embryos. Using the DNA adenine methylase identification method, we identified Dnmt1-binding regions in four- and eight-cell embryos. The unbiased distribution of Dnmt1 peaks in the genic regions (promoters and CpG islands) as well as the absence of a correlation between the Dnmt1 peaks and the expression levels of the peak-associated genes refutes the active participation of Dnmt1 in the transcriptional regulation of genes in the early developmental period. Instead, Dnmt1 was found to associate with genomic retroelements in a greatly biased fashion, particularly with the LINE1 (long interspersed nuclear elements) and ERVK (endogenous retrovirus type K) sequences. Transcriptomic analysis revealed that the transcripts of the Dnmt1-enriched retroelements were overrepresented in Dnmt1 knockdown embryos. Finally, methyl-CpG-binding domain sequencing proved that the Dnmt1-enriched retroelements, which were densely methylated in wild-type embryos, became demethylated in the Dnmt1-depleted embryos. Our results indicate that Dnmt1 is involved in the repression of retroelements through DNA methylation in early mouse development.